Mechanical and thermal properties of the waste low and high density polyethylene-nanoclay composites - Hadi, Arkan J.; AbdulKadir, H. K.; Hadi, Ghassan J.; Kamal, Yusoh; Hasany, S. F. (Oriental Scientific Publishing Company, 2018)
In extension with the previous work, recycling of the waste polyolefins by dissolution/reprecipitation method, has been investigated. The goal of study was to explore the influence of organo-modified/unmodified sodium montmorillonite clays, on the behaviours of waste polyolefins inclusive low density polyethylene (LDPE) and high density polyethylene (HDPE). 1-5 wt % of unmodified (MMT) and Organo-modified clay (OMMT) were added to the polyolefins, to prepare polyolefin-clay nanocomposites by melt intercalation method. X-ray diffraction (XRD) and Field Emission Scanning Electron Microscope (FESEM) were used to estimate the dispersion of clay in the polymer matrices and the morphology of nanocomposites. Thermogravimetric analysis (TGA) and Differential Scanning Calorimetry (DSC) were used to analyse the change in the thermic properties of the waste polyolefins nanocomposites. The XRD and FESEM results showed an intercalated structure in the HDPE and LDPE with Organo-clay nanocomposites, whereas no exfoliation was observed with unmodified clay in both waste HDPE and LDPE, respectively. DSC and TGA, showed an improved thermal behaviours in the HDPE/Organo-clay nanocomposites (3 wt%) clay loading. Melting temperature and crystallization percentage were observed to increase in 1, 2, and 3 wt% loadings. In waste LDPE/clay nanocomposites, no improvement was established in the thermal stability.